The vinylogous aldol reaction of N-Sulfinyl metallodienamines. Issue 7 (14th February 2020) - Yu, Po-Cheng; Chatare, Vijay K.; Patel, Harsh; DeBrosse, Charles; Andrade, Rodrigo B.
Abstract: The discovery and development of the vinylogous aldol reaction of N- sulfinyl metallodienamines with aldehydes and ketones is described. The diastereoselectivity of the reaction, first reported in 2017 as a key step in the total asymmetric synthesis of (−)-albocycline, has been corrected by Mosher ester analysis. The reaction has been optimized and the scope investigated, with yields ranging from 68–89% and diastereomeric ratios as high as 5.9:1. Extensive investigation into the mechanisms affecting stereoselectivity revealed that two stereochemical erosion pathways are operative when using LiHMDS and SnCl4 . A transition state supported by DFT calculations has been advanced to rationalize the stereochemical course of the reaction. Graphical abstract: Image 1 Highlights: Development and optimization of the reaction of N -sulfinyl metallodienamines with aldehydes and ketones. Key step employed in total synthesis of (−)-albocycline. Update and correct the diastereoselectivity of the reaction employing both HPLC and Mosher ester analysis. Yields ranging from 68–89% and diastereomeric ratios as high as 5.9:1. A transition state supported by DFT calculations has been advanced to rationalize the stereochemical course of the reaction.